THE EFFECTS OF ENTREPRENEURIAL ROLE MODEL, ENTREPRENEURIAL EDUCATION, AND INDIVIDUAL ENTREPRENEURIAL ORIENTATION DIMENSIONS ON ENTREPRENEURIAL INTENTION AMONG THE STUDENTS OF A FACULTY OF ECONOMICS AND BUSINESS IN JAKARTA - Cahyadi, Febrianne Clarissa; Selamat, Frangky (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study is to examine whether the entrepreneurial role model, entrepreneurial education, and individual entrepreneurial orientation dimensions affect entrepreneurial intentions among the students of a Faculty of Economics and Business, in Jakarta. The sample was selected using non-probability sampling with a total of 144 respondents. Data was measured using Likert scale and a Structural Equation Model (SEM). Data analysis technique was assisted by SmartPLS software version 3.0. The results show that all variables, which are entrepreneurial role model, entrepreneurial education, and individual entrepreneurial orientation dimensions have positive effects on entrepreneurial intention among the students of a Faculty of Economics and Business in Jakarta.